Determinants of Fraud Financial Statements on State Owned Enterprise - Reski Putri; Rina Yuliastuty Asmara (International Journal of Social Science and Business, 2023)
The lack of control from internal audits and bad organizational culture will lead to fraud and the habit of cheating behavior. The internal audit process is carried out to get certainty of correct and accurate information in the preparation of financial statements following Indonesian IFRS (PSAK). This study aims to inspect the determinants of financial statement fraud with case studies at state-owned-entreprise PT POS Indonesia Regional II. The population of respondents to this research is employees of PT. Pos Indonesia (Persero) works in the Internal Control Unit section of the Jakarta Regional II working area. Data analysis using the Partial Least Square (PLS) approach using the help of the SmartPLS program. PLS is a model of Structural Equation Modeling (SEM) equations based on components or variants. The outcomes showed that internal audit variable had a significant effect on financial reporting fraud. At the same time, the effectiveness or strength of the organization's internal control system and ethical culture do not affect financial reporting fraud. The after-effect of this study can be used to improve existing internal control procedures and organizational ethical culture.